Effect of thickness variation of bituminous layer in the structural responses of flexible pavements - Juliana Pavan Vidotto; Heliana Barbosa Fontenele (Semina: Ciências Exatas e Tecnológicas, 2014)
In this work, a sensitivity analysis was performed to investigate the effect of thickness variation of bituminous layer in the structural responses of flexible pavements and, therefore in performance. For this, it used traffic data from a weigh station located at Km 28 of the Immigrants Highway, at state of Sao Paulo, whose data collection was realized in 2008. The loads deriving from traffic were applied to the computational program ELSYM5 to obtain structural responses related to damage such as fatigue cracks and rutting. With these values, the damage factors were calculated and then the sensitivity analysis related to the thickness variation of bituminous layer was performed. Through the obtained results was concluded that the variation of thickness of bituminous layer have an influence on structural responses, and that damage factors related to fatigue cracks were more sensitive than those factors related to rutting.